Correlation between Mid Upper Arm Muscle Area/Size and Muscle Strength - Tan Yong Bin; Vitriana Vitriana; Titing Nurhayati (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Muscle area/size reflects the true magnitude of muscle tissue changes. Muscle strength is an active tension generated by muscle that depends on its capacity to exert force on an object. The relation between the quantity of muscle area and the amount of muscle strength is suggested. The aim of this study was to analyze the correlation between mid-upper arm muscle area/size and muscular strength.Methods: This analytic study with ten subjects (medical students) who met the inclusion and exclusion criteriawas conducted at the Faculty of Medicine Universitas Padjadjaran in Jatinangor campus from 22th of April to 1st of November 2014. A skinfold calliper was used to measure triceps skinfold while a measuring tape measured the mid-upper arm circumference and a dynamometer measured the muscle strength. A formula was used to determine the mid-upper arm muscle area/size using mid-upper arm circumference and triceps skinfold. The collected data were analyzed statistically using correlation test and simple linear regression.Results: There was a strong correlation between mid-upper arm muscle area/size and muscular strength (correlation cooefficient 0.746). Moreover, the higher the Body Mass Index, the stronger the muscle strength was to some point. If the BMI was more than 25 kg/m2, this findings did not occurred.Conclusions: There is a strong positive correlation between mid-upper arm muscle area/size and arm muscle strength. [AMJ.2016;3(4):590–5]